2014
DOI: 10.1159/000365168
|View full text |Cite
|
Sign up to set email alerts
|

Home Visit Program Improves Technique Survival in Peritoneal Dialysis

Abstract: Background: Peritoneal dialysis (PD) is a home therapy, and technique survival is related to the adherence to PD prescription at home. The presence of a home visit program could improve PD outcomes. We evaluated its effects on clinical outcome during 1 year of follow-up. Methods: This was a case-control study. The case group included all 96 patients who performed PD in our center on January 1, 2013, and who attended a home visit program; the control group included all 92 patients who performed PD on January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 17 publications
0
33
0
3
Order By: Relevance
“…In the traditional monitoring system, patients or their caregivers had to take the card to the dialysis center for treatment visualization and in the case for a new prescription. Once the patients have been trained and the prescription is validated in-person, home visits are mandatory to check general patient conditions [4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the traditional monitoring system, patients or their caregivers had to take the card to the dialysis center for treatment visualization and in the case for a new prescription. Once the patients have been trained and the prescription is validated in-person, home visits are mandatory to check general patient conditions [4]. …”
Section: Discussionmentioning
confidence: 99%
“…In most countries, the cost of home therapies such as peritoneal dialysis (PD) is less and thus, any mechanisms that can increase the uptake of home therapies are likely to result in significant cost savings. It has been proved that the presence of a home visit program could improve PD outcomes [4]. There has been much interest as to whether telemedicine and RM could both increase the uptake of home therapies and improve outcomes by offering continuous medical monitoring, which not only allows verifying patient compliance but also enables identifying problems early and instituting corrective measures.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Also, it has been demonstrated that frequent and regular home visits can help reduce attrition from home dialysis modalities. 30 However, home visits are costly and time consuming, and many centers cannot perform them regularly. Using virtual home visits via RPM may be a preferable substitute to an in-person home visit.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, excluding patients who may have difficulty performing the procedure (e.g., stroke, poor vision, and previous abdominal surgery), as many as 85% of stage 5 chronic kidney disease (CKD) patients are medically eligible for peritoneal dialysis [ 1 ]. However, patients on PD comprise only 10% of the entire end-stage renal disease (ESRD) population and the percentage of African-American and Hispanic ESRD patients treated with peritoneal dialysis has been consistently lower than that of White dialysis patients [ 2 ]. Surveys show that only two-thirds of ESRD patients beginning maintenance dialysis are presented with peritoneal dialysis as an option.…”
Section: Introductionmentioning
confidence: 99%